2023
DOI: 10.1111/jpn.13886
|View full text |Cite
|
Sign up to set email alerts
|

Fat deposition, fatty acid profiles, antioxidant capacity and differentially expressed genes in subcutaneous fat of Tibetan sheep fed wheat‐based diets with and without xylanase supplementation

Li Zhou,
Sayed Haidar Abbas Raza,
Zhanhong Gao
et al.

Abstract: Xylanase, an exogenous enzyme that plays an essential role in energy metabolism by hydrolysing xylan into xylose, has been shown to positively influence nutrient digestion and utilisation in ruminants. The objective of this study was to evaluate the effects of xylanase supplementation on the back‐fat thickness, fatty acid profiles, antioxidant capacity, and differentially expressed genes (DEGs) in the subcutaneous fat of Tibetan sheep. Sixty three‐month‐old rams with an average weight of 19.35 ± 2.18 kg were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…By decreasing the ruminal pH, increasing dietary wheat increase the potential risk for subacute ruminal acidosis in goats (Li et al, 2014). In recent years, the dietary modulation of livestock, epecially in sheep, has gained significant attention for its impact on meat quality and health‐related aspects (Zhou et al, 2023). Currently, as little research accurately reported the effects of different levels of dietary wheat in Tibetan sheep.…”
Section: Introductionmentioning
confidence: 99%
“…By decreasing the ruminal pH, increasing dietary wheat increase the potential risk for subacute ruminal acidosis in goats (Li et al, 2014). In recent years, the dietary modulation of livestock, epecially in sheep, has gained significant attention for its impact on meat quality and health‐related aspects (Zhou et al, 2023). Currently, as little research accurately reported the effects of different levels of dietary wheat in Tibetan sheep.…”
Section: Introductionmentioning
confidence: 99%